Financial services sector protection and homeland security - Spellman, Frank R. (Homeland security series (Lanham, Md.), 2019)
"The financial services sector is critical to the economy and represents a vital component of our nation's critical infrastructure. Financial Services Sector Protection and Homeland Security provides readers with an understanding of the challenges and potential threats faced by this sector"--